1916 and all that: Lessons from a decade of centenaries for Ireland and the UK. Issue 4 (March 2016) - Kidd, Colin
Abstract : As we approach what might be the crescendo of a decade of politically loaded centenaries, Colin Kidd considers how the foundational events of 1912‐1922 affected the development of Ireland's politics and its relationship with the UK, and finds lessons there for the British left on how to engage with nationalism as a live and legitimate political sentiment.